An extraordinary year: strikes, uprisings and circulation of ideas in Brazil in 1917 - Toledo, Edilene (2017)
This article analyzes, from original research and carried out studies, the strikes and revolts that took place in São Paulo, Rio de Janeiro, Recife, Porto Alegre and other cities of Brazil in 1917 and their demands, the participation of workers and anarchists and socialists militants in these events and the circulation of political ideas in the period, especially the first impacts on the country of the revolutions that occurred in Russia that year and how these new revolutionary ideas began to transform political groups and workers' organizations. The strikes of that year had a basic role for the later development of the labor movement and the labor struggles in Brazil.